Measles outbreak in South of iran, where vaccine coverage was high: a case-series study. - Mohsen Moghadam; Parvin Afsarkazerooni; Mostafa Ebrahimi; Mahboobe Soltani; Ardeshir Razmpoor; Esmaei Pirasteh; Alireza Mirah-Madizadeh (Tehran University of Medical Sciences, 2014)
Measles is a highly contagious viral disease that remains an important cause of mortality among children despite the availability of a safe and effective vaccine around the world. We aimed this study to show a measles out-break occurring.In early 2012, a report of measles outbreak was recorded on center for disease control (CDC) of Fars province, south of Iran. With this case-series study, characteristics of cases and network transition model were described.The primary case was an Afghan refugee who is likely to carry the measles virus from its country or from anywhere in Iran to Koordeh, a small village in south of Iran. Followed by the Afghan case, 6 secondary and tertiary cases including rural health worker, were occurred. Except a case of 35 year old, in which her vaccination status was unknown, all cases has had adherence to vaccination protocol.More immunologic and vaccine quality investigations are needed to find the main cause of the outbreak. Nonetheless, due to the warm weather, probable bad temperature management of cold chain and technical problem in vaccination are the main suspicious reasons of the outbreak.